A Cross-Cultural Examination of SNS Usage Intensity and Managing Interpersonal Relationships Online: The Role of Culture and the Autonomous-Related Self-Construal - Lee, Soon Li; Kim, Jung-Ae; Golden, Karen Jennifer; Kim, Jae-Hwi; Park, Miriam Sang-Ah (Frontiers in Psychology, 2016)
Perception of the autonomy and relatedness of the self may be influenced by one’s experiences and social expectations within a particular cultural setting. The present research examined the role of culture and the Autonomous-Related self-construal in predicting for different aspects of Social Networking Sites (SNS) usage in three Asian countries, especially focusing on those aspects serving interpersonal goals. Participants in this cross-cultural study included 305 university students from Malaysia (n = 105), South Korea (n = 113), and China (n = 87). The study explored specific social and interpersonal behaviors on SNS, such as browsing the contacts’ profiles, checking for updates, and improving contact with SNS contacts, as well as the intensity of SNS use, hypothesizing that those with high intensity of use in the Asian context may be doing so to achieve the social goal of maintaining contact and keeping updated with friends. Two scales measuring activities on other users’ profiles and contact with friends’ profiles were developed and validated. As predicted, some cross-cultural differences were found. Koreans were more likely to use SNS to increase contact but tended to spend less time browsing contacts’ profiles than the Malaysians and Chinese. The intensity of SNS use differed between the countries as well, where Malaysians reported higher intensity than Koreans and Chinese. Consistent with study predictions, Koreans were found with the highest Autonomous-Related self-construal scores. The Autonomous-Related self-construal predicted SNS intensity. The findings suggest that cultural contexts, along with the way the self is construed in different cultures, may encourage different types of SNS usage. The authors discuss study implications and suggest future research directions.